Characterization of gas metal arc welded A 572 GR 50 steel - Kumar H.; Prasad R.; Kumar P.; Deo M.; Ravindra A. (My University, 2025)
Gas metal arc welding (GMAW) is a versatile welding technique and hence used in almost all industrial segment. The process parameters greatly affect mechanical properties in heat affected zone (HAZ) and weld bead zone. In the present investigation, optimized process parameters were selected after rigorous literature review. The parameters current, gas flow rate and welding speed were 170 ampere, 14 lit/min and 1.25 mm/sec respectively. The welded structure was characterized for microstructural features in different zones through optical microscopy. The mechanical properties of the welded plates were analyzed in terms of microhardness and tensile strength. Results showed higher hardness in the weld bead region with respect to base metal and HAZ region. The strengths (yield and ultimate tensile strength) both decreased in weld bead region because of the grain coarsening. © 2023 Author(s).